2023
DOI: 10.1007/s40544-022-0707-5
|View full text |Cite
|
Sign up to set email alerts
|

Review of the evolution and prevention of friction, wear, and noise for water-lubricated bearings used in ships

Abstract: With the development of green tribology in the shipping industry, the application of water lubrication gradually replaces oil lubrication in stern bearings and thrust bearings. In terms of large-scale and high-speed ships, water-lubricated bearings with high performance are more strictly required. However, due to the lubricating medium, water-lubricated bearings have many problems such as friction, wear, vibration, noise, etc. This review focuses on the performance of marine water-lubricated bearings and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 238 publications
0
7
0
Order By: Relevance
“…The complexity of loading conditions of the bearing increases with uncertain environment underwater [1]. To meet the requirements of green shipping, these bearings could be lubricated with water [2]. Water has very low viscosity compared to other standard stern tube lubricants and therefore lubricant starvation could occur.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of loading conditions of the bearing increases with uncertain environment underwater [1]. To meet the requirements of green shipping, these bearings could be lubricated with water [2]. Water has very low viscosity compared to other standard stern tube lubricants and therefore lubricant starvation could occur.…”
Section: Introductionmentioning
confidence: 99%
“…Green tribology has emerged as a prominent area of focus within the field of contemporary tribology [4][5][6]. Water-lubricated bearings based on water-based lubrication have attracted significant attention among scholars due to their cost-effectiveness, environmental friendliness, and easy maintenance [7][8][9]. Water exhibits numerous distinctive properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the limited viscosity and carrying capacity of pure water hinder the formation of a comprehensive lubricating film and hydrodynamic lubrication in water-lubricated bearings operating under low speed and heavy load conditions [11][12][13]. Furthermore, it has been observed that the utilization of water-based lubrication can lead to a corrosive impact on mechanical components composed of steel and its alloys [9]. The aforementioned deficiencies have a significant impact on the dependability of subaquatic equipment and severely restrict the feasible utilization of water-lubricated bearings.…”
Section: Introductionmentioning
confidence: 99%
“…In these mediums, a variety of corrosive microorganisms thrive, including sulfate-reducing bacteria, iron bacteria, methanogens, acid-producing bacteria and so on [5][6][7][8]. In particular, the motion components lubricated with water often operate in mixed and even boundary lubrication regimes [9]. The tribo-corrosion of the metallic components is a significant challenge regarding the lifespan and reliability of the equipment [10,11].…”
Section: Introductionmentioning
confidence: 99%